Prevalence Of Anemia and Its Systemic Effects in Women with Chronic Abnormal Uterine Bleeding - Aysha Iqbal, Abeerah Zafar, Sehrish Muzafar, Iffat Jabeen, Kinza Ijaz, Sidra Javed (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Chronic abnormal uterine bleeding (AUB) is a common gynecological disorder and a major cause of iron deficiency anemia in women of reproductive age. Persistent blood loss not only reduces hemoglobin levels but also leads to systemic manifestations that significantly impair physical functioning and quality of life. Objective: To determine the prevalence and severity of anemia and to evaluate its systemic effects among women with chronic abnormal uterine bleeding presenting to a tertiary care hospital. Methods: This hospital-based cross-sectional study was conducted in the Gynaecology Unit-II, Sahiwal Teaching Hospital, Pakistan, from June 2022 to May 2023. A total of 90 women aged 18–50 years with chronic AUB of at least six months’ duration were enrolled. Detailed clinical history and physical examination were performed. Hemoglobin levels and red cell indices were measured using automated hematology analysis. Anemia was defined as hemoglobin <12 g/dL and categorized as mild, moderate, or severe. Systemic effects including fatigue, weakness, exertional dyspnea, palpitations, dizziness, headache, and functional limitation were documented. Data were analyzed using descriptive and comparative statistics. Results: Anemia was detected in 62 women, yielding a prevalence of 68.9%. Mild anemia was present in 31.1%, moderate anemia in 26.7%, and severe anemia in 11.1% of participants. Microcytic anemia was the predominant pattern, indicating iron deficiency. Systemic manifestations were significantly more frequent among anemic women, particularly fatigue (83.9%), generalized weakness (74.2%), exertional dyspnea (50.0%), and reduced daily functional capacity (61.3%). The severity of symptoms increased with worsening anemia. Conclusion: Anemia is highly prevalent in women with chronic AUB and is associated with considerable systemic morbidity. Early screening and integrated management of anemia should be a routine component of care in these patients. Keywords: Abnormal uterine bleeding; Anemia; Iron deficiency; Systemic effects; Women; Chronic bleeding